Always, better and control - vital, essential, desirable matrix analysis of the drug store of a tertiary care teaching hospital of North India - Gupta, Ravi K.; Makkar, Namrata; Shamdasani, Sonali (International Journal of Research in Medical Sciences, 2019)
Background: Substantial improvement can be brought about in the hospital inventory and drug expenditure by inventory control techniques. These include ABC (always, better and control), VED (vital, essential and desirable) and ABC-VED matrix analysis. The objective of the study was to categorize the drugs based on cost and criticality and identify those which require stringent managerial control. Methods: ABC analysis according to drug expenditure, VED analysis according to criticality of the drugs, ABC-VED matrix analysis to classify drugs into category I, II and III was done for drug store of a tertiary care teaching hospital of North India for the period of April, 2018 to March, 2019. Results: The total number of the drug items used by the drug store was 315. The total drug expenditure was Rs. 9,61,29,859. By ABC analysis, it was found that 15.24%, 22.54% and 62.22% items belonged to A, B and C category respectively, accounting for 70%, 20% and 10% of Annual Drug Expenditure (ADE). VED analysis showed that 31.11%, 60.32% and 8.57% were V, E, and D category items respectively, accounting for 30.44%, 57.12% and 12.44% of ADE. By ABC-VED matrix analysis, 42.86%, 52.38% and 4.76% items were category I, II and III items respectively, accounting for 78.91%, 20.15% and 0.94% of ADE. Conclusions: The study depicted the items belonging to category I which requires top managerial control, also the items belonging to categories II and III which require control by middle and lower managerial level respectively.